O programa de aquisição de alimentos (PAA) e o programa nacional de alimentação escolar (PNAE) no município de Dracena-SP - Colnago, Ellen Tamires Pedriali [UNESP] (2015)
Food and Nutrition Security (FNS) is gaining more international prominence by becoming a recurring theme in several countries. Nationally, a milestone of this concern about the feeding of people who are in a situation of food insecurity was given under President Luiz Inacio Lula da Silva who, in 2003, created the Zero Hunger Program that had, between actions provided, the Food Acquisition Program (PAA). In 2009, consolidated also, by law, the National School Feeding Programme (PNAE). Starting from the creation of these two programs, it was established, therefore, a marketing channel for family farms, from the delivery of products aimed populations that have food insecurity if the social assistance entities served by the PAA and elementary schools and Average served by PNAE. This academic paper aims to analyze the importance these programs make for social and economic reproduction of family farmers organized in associations. The area of study covers Dracena city in São Paulo state, in which the empirical results obtained through development and implementation of interview scripts and questionnaires demonstrate that: agronomists emphasize the importance of technical assistance, especially of Agriculture to House the development of programs, along with the collective organizations, in the case in particular associations of producers; the president of the association studied also shares this idea, as well as advocates greater participation of producers in the PNAE...